2015
DOI: 10.1021/acs.langmuir.5b01062
|View full text |Cite
|
Sign up to set email alerts
|

Particle Segregation at Contact Lines of Evaporating Colloidal Drops: Influence of the Substrate Wettability and Particle Charge–Mass Ratio

Abstract: Segregation of particles during capillary/convective self-assembly is interesting for self-stratification in colloidal deposits. In evaporating drops containing colloidal particles, the wettability properties of substrate and the sedimentation of particles can affect their accumulation at contact lines. In this work we studied the size segregation and discrimination of charged particles with different densities. We performed in-plane particle counting at evaporating triple lines by using fluorescence confocal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 32 publications
0
11
0
Order By: Relevance
“…The coffee‐ring effect is manifested in systems with diverse constituents (ranging from large colloids to nanoparticles), and can be exploited to construct many interesting patterns from various functional materials. [ 35,41 43,110–117 ] Gu et al used the above effect to produce self‐assembled circular‐structure colored contact lenses on a hydrophilic template ( Figure a). [ 39 ] The as‐prepared lenses displayed variable colors under light illumination, preventing the potential harm that can be inflicted on the eyes due to wearing traditional colored contact lenses.…”
Section: Colloidal Assembly On Substrates With Distinct Wettabilitymentioning
confidence: 99%
See 1 more Smart Citation
“…The coffee‐ring effect is manifested in systems with diverse constituents (ranging from large colloids to nanoparticles), and can be exploited to construct many interesting patterns from various functional materials. [ 35,41 43,110–117 ] Gu et al used the above effect to produce self‐assembled circular‐structure colored contact lenses on a hydrophilic template ( Figure a). [ 39 ] The as‐prepared lenses displayed variable colors under light illumination, preventing the potential harm that can be inflicted on the eyes due to wearing traditional colored contact lenses.…”
Section: Colloidal Assembly On Substrates With Distinct Wettabilitymentioning
confidence: 99%
“…This non‐lithographic approach could create patterned microstructures in a simple and cost‐effective manner. The coffee‐ring effect was used in many interesting applications such as particle separation [ 114–116 ] and disease diagnostics. [ 117 ] Ho's group [ 115 ] elucidated the physics of coffee‐ring effect‐driven particle separation (Figure 4f) by observing droplet vaporization on a pre‐cleaned cover glass.…”
Section: Colloidal Assembly On Substrates With Distinct Wettabilitymentioning
confidence: 99%
“…Recently, Noguera-Marín et al studied the segregation and discrimination of charged particles with different densities during solvent evaporation. Changing substrate wettability and particle charge-mass ratios in low-ionic-strength solutions influenced the segregation of binary colloidal suspensions . The highly negatively charged particles were observed to transport and deposit in the vicinity of the contact line at a faster pace than those with less particle charge density.…”
Section: Introductionmentioning
confidence: 98%
“…Further investigation showed that this mechanism was also dependent on the charge-mass ratio of the particles. 17 Segregation between particles was observed due to greater charge-mass ratios resulting in stronger resistance to sedimentation. Anyfantakis et al 18 also attempted to suppress the coffee-ring effect via particle interactions.…”
Section: Introductionmentioning
confidence: 99%